FAKTOR-FAKTOR YANG MEMPENGARUHI ISLAMIC SOCIAL REPORTING PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR PADA INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2011-2012 - Tria Karina Putri; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
The aim of this study is to obtain an empirical evidence about factor that affect Islamic Social Reporting (ISR) in company’s annual report. The factors that used in this study such as: industry size, profitability, company type, and islamic securities. Measurement of Islamic Social Reporting is based on islamic social reporting categories that used to calculate the Islamic Social Reporting Index as seen from the company’s annual report.Populations in this study are all companies that listed in Indonesia Sharia Stock Index (ISSI) exchange in 2011-2012. The sampling method in this study is purposive sampling. The total number of samples in this study were 142 research samples. The analytical techniques was conducted by multiple regression method and also classical assumption test.The analysis showed that industry size, profitability, company type, and islamic securities significantly positive influence the Islamic Social Reporting (ISR) in Indonesia. Meanwhile, profitability had no significant effect to the Islamic Social Reporting (ISR) in Indonesia.